Desarrollo de competencias tecnológicas en docentes. Una mirada desde la Andragogía (2016)
Firstly, this article seeks to examine the literature around the theory of andragogy, which is understood as the science that studies adult education, as well as examining who has contributed to its conceptualisation and what principals are at its foundation. Secondly, the technological competencies in teacher training are looked at, seen as a fundamental aspect of an adult population, whilst also looking at the aspects that justify its relevance as a method. To conclude, it puts forward the perspective of research which has linked the development of said competencies in an adult population, using the principals that underpin the andragogic model whilst examining the results.